Effects of Isosakuranetin on Pharmacokinetic Changes of Tofacitinib in Rats with N-Dimethylnitrosamine-Induced Liver Cirrhosis - Bae, Sung Hun; Choi, Hyeon Gyeom; Park, So Yeon; Chang, Sun Young; Kim, Hyoungsu; Kim, So Hee (Pharmaceutics, 2022)
Tofacitinib, a Janus kinase 1 and 3 inhibitor, is used to treat rheumatoid arthritis. It is mainly metabolized by the cytochromes p450 (CYP) 3A1/2 and CYP2C11 in the liver. Chronic inflammation eventually leads to cirrhosis in patients with rheumatoid arthritis. Isosakuranetin (ISN), a component of Citrus aurantium L., has hepatoprotective effects in rats. This study was performed to determine the effects of ISN on the pharmacokinetics of tofacitinib in rats with N-dimethylnitrosamine-induced liver cirrhosis (LC). After intravenous administration of 10 mg/kg tofacitinib to control (CON), LC, and LC treated with ISN (LC-ISN) rats, the total area under the plasma concentration–time curves (AUC) from time zero to infinity increased by 158% in LC rats compared to those in CON rats; however, the AUC of LC-ISN rats decreased by 35.1% compared to that of LC rat. Similar patterns of AUC changes were observed in the LC and LC-ISN rats after oral administration of 20 mg/kg tofacitinib. These results can be attributed to decreased non-renal clearance (CLNR) and intestinal intrinsic clearance (CLint) in the LC rats and increased intestinal and hepatic CLint in the LC-ISN rats. Our findings imply that ISN treatment in LC rats restored the decrease in either CLNR or CLint, or both, through increased hepatic and intestinal expression of CYP3A1/2 and CYP2C11, which is regulated by the induction of pregnane X receptor (PXR) and constitutive androstane receptor (CAR).
Keywords: CAR; CYP2C11; CYP3A1/2; isosakuranetin; liver cirrhosis; pharmacokinetics; PXR; tofacitinib